EXPERIMENTAL RESEARCH ON ULTRASONIC GUIDED WAVES DEFECT CLASSIFICATION BASED ON FRACTIONAL DIMENSION AND BP NEURAL NETWORK - WU Jing; RAO ZiYu; SHEN YuChi; LIAO Bin; Zhang WeiWei; ZOU HouDe; MA HongWei (Jixie qiangdu)
In recent years, ultrasonic guided waves technology has been widely used in nondestructive pipeline detection. However, the weak and insignificant defect echoes caused by the different types of tiny defects such as cracks, void, and dent deformation makes it difficult to identify and classify different types of miero defects. In order to identify the types of different tiny defects, the sensitivity of Duffing system to weak periodie signals was exploited and a signal feature classification method based on the dynamic index fractal dimension of the Duffing system and the back propagation (BP) neural network was proposed. By extracting the fractal dimension、 wavelet cocfficient and time domain signal parameters of the Duffing oscillator after inputting the defect signal to be tested as the characteristic parameters of the echo signal, inputting the BP neural network to complete the construction of the BP neural network, realizing the learning of the weak ultrasonie guided wave signal, classification. The numerical simulation and experimental verification show that the recognition accuracy is significantly improved by taking the fractal dimension of chaos index of three Duffing oscillators into consideration. The accuracy of numerical simulation is increased from 86.35% to 91.85%、 and the accuracy of experimental verification is increased from 83.16% to 86.06%. The numerical simulation and experiment verify that the combination of fractal dimension and BP neural network can effectively improve the identification of pipeline features and defects. The innovative use of fractal as the feature input of BP neural network effectivel y improves the accuracy of classification, facilitating identification and accurate classification, particularly in cases of insufficient experimental data or difficult detection scenarios invol ving small defects in the pipeline. The novel classification method that has been proposed has important significance for the pipeline defects classification and accidents prevention.